The Phosphodiesterase Inhibitor Tadalafil Promotes Splenic Retention of Plasmodium falciparum Gametocytes in Humanized Mice - Barbieri, Daniela; Gomez, Lina; Royer, Ludivine; Dupuy, Florian; Franetich, Jean-François; Tefit, Maurel; N’Dri, Marie-Esther; Mazier, Dominique; Silvie, Olivier; Moreno-Sabater, Alicia; Lavazec, Catherine (Frontiers in Cellular and Infection Microbiology, 2022)
The persistence of erythrocytes infected with Plasmodium falciparum gametocytes in the bloodstream is closely related to the modulation of their mechanical properties. New drugs that increase the stiffness of infected erythrocytes may thus represent a novel approach to block malaria parasite transmission. The phosphodiesterase inhibitor tadalafil has been shown to impair the ability of infected erythrocytes to circulate in an in vitro model for splenic retention. Here, we used a humanized mouse model to address in vivo the effect of tadalafil on the circulation kinetics of mature gametocyte-infected erythrocytes. We show that stiff immature gametocyte-infected erythrocytes are retained in the spleen of humanized mice at rates comparable to that of the in vitro model. Accordingly, tadalafil-induced stiffening of mature gametocyte-infected erythrocytes impairs their circulation in the bloodstream and triggers their retention by the spleen. These in vivo results validate that tadalafil is a novel drug lead potentially capable of blocking malaria parasite transmission by targeting GIE mechanical properties.